157 Neurocognitive Decline and Recovery in Patients Undergoing Microsurgical vs Endovascular Treatment of Unruptured Intracranial Aneurysms. (August 2015) - Caveney, Angi; Pandey, Aditya S.; Langenecker, Scott A.; Gabriel, Laura; Ortiz, J. Alexis; Huq, Nadia; Bhaumik, Runa; Thompson, Byron Gregory; Giordani, Bruno J.; Auer, Donna L.; Morgenstern, Lewis
Abstract : INTRODUCTION: Neurocognitive changes postsurgical clipping (SC) or endovascular coiling (EC) of unruptured aneurysms is not well studied. We aim to understand whether patients who undergo EC perform better on neurocognitive assessments in comparison with patients who undergo SC, and if such a difference exists how long the difference persists. METHODS: This is a single-center, prospective, longitudinal study with patients divided into the microsurgical, endovascular, and healthy control (HC) groups. All three groups underwent baseline neurocognitive assessments as well as post-procedure evaluations at 2 to 3 weeks, 3 months, 6 months, and 12 months. Two mixed-effects models (postprocedure decline and subsequent recovery) were computed for each dependent variable and controlling for age, IQ, sex, and complications. RESULTS: Included were 50 clipped, 36 coiled, and 43 control patients. Anterior communicating artery (ACOM) and middle cerebral artery (MCA) aneurysms comprised 64% of the clipped patients, while 86.1% of the coiled aneurysms were located within the posterior circulation or paraclinoid region. Symptomatic stroke occurred within 1 patient in the clipped group and none within the coiled group. At 2 weeks postprocedure, the SC group showed significantly greater decline than the HC group on measures of verbal learning/memory, fine motor dexterity, and executive functioning. The SC group also demonstrated significantly greater decline than the EC group on measures of executive functioning and flexibility. The SC group showed greater decline than both other groups on measures of simple reaction time, verbal fluency, working memory, and executive functioning. At 3 to 6 months postprocedure, the SC group no longer exhibited these neurocognitive deficits. CONCLUSION: The SC group had greater decline in neurocognitive functioning but were generally able to return to baseline functioning within 3 to 6 months.